The Influence of Augmented Reality Technology Models on Floor Exercise Movement Skills in Junior High School Students. - Sugiarto, Tatok; Darmawan, Arief; Sugiyanto, Sugiyanto; Priyohutomo, Ahadi; Sigit, Cahyo Nugroho (Media Ilmu Keolahragaan Indonesia, 2023)
Abstract. The achievement of a movement learning process will run well and maximally if it includes the influence of new media or teaching and is accompanied by appropriate technology. The aim of this research is to find out the effectiveness of Augmented Reality (AR) in floor exercise. This research method uses an experimental approach with a randomized control group pretest and posttest design. The subjects in this study consisted of 10 children in each control and experimental group, making a total of 20 children aged 13-14 years. The results of this research show an average value of 40.90 in the control group and 100.50 in the experimental group. It can be concluded that there was an increase in floor exercise movement skills for front rolls and back rolls in both groups by 59.6%. In the paired samples test, the Sig (2-tailed) value was 0.000 0.005, indicating significant differences in floor exercise skills between the control and experimental groups. This research demonstrates the effectiveness of AR models in improving floor exercise skills. The novelty of this research lies in its application of AR technology in physical education, which has not been extensively explored. The implications of this study suggest that AR technology can significantly enhance learning experiences and outcomes in physical education, providing a valuable tool for educators and students alike.Abstract in Indonesia. Ketercapaian sebuah proses pembelajaran gerak akan berjalan dengan baik dan maksimal jika di dalamnya terdapat pengaruh media atau pengajaran yang baru serta disertai dengan teknologi yang tepat guna. Tujuan penelitian ini adalah untuk mengetahui efektivitas Augmented Reality (AR) dalam senam lantai. Metode penelitian ini menggunakan pendekatan eksperimental dengan desain kelompok kontrol acak pretest dan posttest. Subjek dalam penelitian ini terdiri dari 10 anak di setiap kelompok kontrol dan eksperimen, dengan total 20 anak berusia 13-14 tahun. Hasil penelitian ini menunjukkan nilai rata-rata sebesar 40,90 pada kelompok kontrol dan 100,50 pada kelompok eksperimen. Dapat disimpulkan bahwa terdapat peningkatan keterampilan gerak senam lantai untuk guling depan dan guling belakang di kedua kelompok sebesar 59,6%. Pada uji sampel berpasangan, nilai Sig (2-tailed) sebesar 0,000 0,005, yang menunjukkan adanya perbedaan signifikan dalam keterampilan senam lantai antara kelompok kontrol dan eksperimen. Penelitian ini menunjukkan efektivitas model AR dalam meningkatkan keterampilan senam lantai. Kebaruan dari penelitian ini terletak pada penerapan teknologi AR dalam pendidikan jasmani, yang belum banyak dieksplorasi. Implikasi dari penelitian ini menunjukkan bahwa teknologi AR dapat secara signifikan meningkatkan pengalaman dan hasil belajar dalam pendidikan jasmani, memberikan alat yang berharga bagi pendidik dan siswa.